Dravet syndrome: novel insights into SCN1A-mediated epileptic neurodevelopmental disorders within the molecular diagnostic-therapeutic framework - Zhang, Guirui; Huang, Shupeng; Wei, Mingzhen; Wu, Yongmo; Xie, Zhengyi; Wang, Jin (Frontiers in Neuroscience, 2025)
Dravet Syndrome (DS), a rare genetic encephalopathy characterized by severe drug-resistant epilepsy and progressive neurodevelopmental regression in infancy, is caused by de novo mutations in the SCN1A gene on chromosome 2q24 in over 80% of cases. This review synthesizes current insights into its molecular pathogenesis, precision diagnostics, and therapeutic innovations: SCN1A mutations disrupt Nav1.1 sodium channel expression and membrane trafficking in GABAergic interneurons through transcriptional dysregulation, pre-mRNA splicing defects, and gating dysfunction, thereby impairing inhibitory synaptic transmission and disrupting brainwide excitatory-inhibitory balance. Notably, polygenic interactions (e.g., DEPDC5, CHD2 variants), astrocytic calcium signaling aberrations, and mitochondrial metabolic deficits synergistically exacerbate network hyperexcitability. Diagnostic advancements include a stratified framework integrating early febrile seizure phenotypes, comprehensive SCN1A sequencing (including deep intronic variants), and multimodal assessments (e.g., γ-band EEG power analysis and hippocampal volumetry), which significantly accelerate clinical diagnosis and reduce misdiagnosis. Therapeutic strategies are evolving from empirical seizure control to mechanism-targeted interventions: antisense oligonucleotides (ASOs) restore SCN1A transcript integrity by blocking pathogenic exon inclusion; adeno-associated virus (AAV9)-mediated activation of GABAergic neuron-specific SCN1A promoters and CRISPR/dCas9-driven endogenous Nav1.1 upregulation have both been shown to improve inhibitory synaptic function and elevate seizure thresholds in preclinical models. Additionally, novel molecules such as the Nav1.1-selective agonist Hm1a and 5HT2BR receptor modulators offer new avenues by remodeling neuronal electrophysiology and neurotransmitter homeostasis. By dissecting the multi-dimensional molecular networks underlying DS and highlighting interdisciplinary integration of diagnostic-therapeutic technologies, this review provides a theoretical foundation for developing SCN1A-centric precision medicine, advocating a shift from symptomatic management to mechanism-driven interventions in clinical practice.